MERAJUT KESUKSESAN BERAS LOKAL: ANALISIS MENDALAM STRATEGI PEMASARAN BERAS MBAY DI KABUPATEN FLORES TIMUR - Byre, Rafael Octavianus (ANALISIS, 2024)
Consumer perception of Mbay rice and its marketing strategy in East Flores Regency is the subject of this study. This study involved one hundred respondents through questionnaires and interviews. A combination of quantitative and qualitative methods was used. The results of multiple linear regression analysis obtained product, promotion and location variables have a significant effect on consumer purchasing decisions (adjusted R2 = 0.528). SWOT analysis provides recommendations for new strategies. These include increasing digital marketing, improving product quality, increasing prices, building distribution networks, and creating a premium image. STP analysis presents demographic and geographic segments, focusing on middle and upper income women aged 18 to 50 years. The positioning of Mbay rice should prioritize product quality and competitive prices. It is hoped that by implementing this strategy, Mbay Rice will gain a larger market share and strengthen its position in the local market in East Flores Regency.